Resepsi Al-Qur’an dalam Budaya Tuli : Studi Komunitas Gerkatin Gorontalo - Moh. Azwar Hairul (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2022)
The ability to read the Qur'an is based on the perfection of reciting each letter and knowing the punctuation of each verse. But not so with the deaf, reading aloud is a complicated thing and can even be said to be impossible for them. The interaction of the deaf with the Qur'an is done through sign language. This inclusion awareness is carried out by the Deaf Welfare Movement (Gerkatin) Gorontalo which focuses on eradicating illiteracy in the Qur'an. This study aims to describe the motivational experience of the interaction of the deaf with the Qur'an. This research is qualitative with a phenomenological approach and uses Herbert Blumer's symbolic interaction theory as an analytical tool. The results of this study indicate that although the deaf does not use sound when reading and memorizing the Qur'an, the deaf can still understand and interpret it. This can be seen from the interaction of the deaf with the Koran through the stages of 1) memorizing the Qur'an sign letters 2) writing the Qur'an sign letters 3) memorizing letters and their punctuation 4) understanding verses. In this case, the verses of the Qur'an are manifested through sign symbols that are moved by the deaf.